No evidence of an increase in the incidence of norovirus gastroenteritis hospitalizations in young children after the introduction of universal rotavirus immunization in Israel - Khitam Muhsen; Eias Kassem; Uri Rubenstein; Sophy Goren; Moshe Ephros; Lester M. Shulman; Dani Cohen (Taylor & Francis Group, 2019)
Following the introduction of universal immunization against rotavirus, concerns were raised regarding pathogen-replacement of rotavirus by norovirus. The study aim was to examine the incidence and characteristics and norovirus gastroenteritis before and after the introduction of universal rotavirus immunization in Israel. We studied 1179 stool samples collected between November 2007 and December 2014 for a prospective hospital-based surveillance study of children aged 0-59 months hospitalized for gastroenteritis. A real-time RT-PCR assay was used to identify genogroup II (GII) norovirus in extracted fecal RNA samples. Overall, the weighted percentage of norovirus positive patients was 10.9%. Norovirus positivity was similar in the pre-universal rotavirus immunisation years (2008-2010) and the universal years (2011-2014), the respective average annual incidence of norovirus gastroenteritis was 1.6 (95% CI 0.6-2.3) per 1000 and 1.1 (95% CI 0.8-1.4) per 1000 children. Rotavirus was detected in 36.8% and 19.6% of the patients in the pre-vaccine years and the universal vaccine years, with an estimated incidence of 5.5 (95% CI 3.4-7.6) per 1000 and 2.1 (95% CI 1.6-2.7) per 1000 children, respectively. Most patients (59.1%) with norovirus gastroenteritis were infants aged 0-11 months. Norovirus was detected all year round with a significant 3-month peak from September through November. In conclusion, norovirus continues to be a leading cause of acute gastroenteritis associated with hospitalizations in young children. Future norovirus vaccines should target young infants. There was no evidence of pathogen-replacement by norovirus following the introduction of universal rotavirus immunization in Israel.